2020
DOI: 10.1186/s12883-020-01760-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 is associated with acute concussion in military combat personnel

Abstract: Background: Concussion is the most common type of TBI, yet reliable objective measures related to these injuries and associated recovery processes remain elusive, especially in military personnel. The purpose of this study was to characterize the relationship between cytokines and recovery from acute brain injury in active duty service members. Inflammatory cytokines (IL-6, IL-10, and TNFα) were measured acutely in blood samples within 8 h following a medically diagnosed concussion and then 24 h later. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…We found reductions in pro-inflammatory cytokines IL-6 and TNF-ɑ, and no change in the anti-inflammatory cytokine IL-10. These results are also consistent with existing literature, as other studies have reported improvements in pro-inflammatory cytokines with improved sleep, including treatment of sleep apnea [ 60 , 78 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found reductions in pro-inflammatory cytokines IL-6 and TNF-ɑ, and no change in the anti-inflammatory cytokine IL-10. These results are also consistent with existing literature, as other studies have reported improvements in pro-inflammatory cytokines with improved sleep, including treatment of sleep apnea [ 60 , 78 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, one of the 4 biomarkers in the 4-plex, UCHL1, was unable to be included in our analyses. However, NfL and tau are both widely accepted markers of neuronal injury [ 60 , 76 , 77 ]. Further, despite the small sample size, peripheral markers of neuronal injury and neuroinflammation such as NfL and tau still showed trends towards statistical significance in directions consistent with the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 acts as a regulator of inflammatory procedures by inducing either a pro- or anti-inflammatory response [ 11 ]. IL-6 levels are typically upregulated shortly after a mTBI event [ 21 , 22 ], and can remain elevated for weeks or months following such an injury [ 18 , 23 ]. Acutely elevated IL-6 levels are associated with greater symptom duration and severity in mTBI [ 17 , 21 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our previous review has demonstrated that depression and anxiety are associated with elevated TNF-α, IL-6, IFN-α, and C-Reactive Protein (CRP) levels [ 9 ]. Overall, the most common systemic cytokines associated with mTBI include IL-6 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], TNF-α [ 20 , 23 , 24 , 25 ], IL-10 [ 20 , 26 ], IL-1β [ 19 , 20 ], Interleukin-8 (IL-8) [ 20 , 25 ], Interferon Gamma (IFN-γ) [ 20 , 25 ], Interleukin-1RA (IL-1RA) [ 17 , 21 ], Interleukin-4 (IL-4) [ 20 ], and C–C motif chemokine ligand 2 (CCL2) [ 19 , 27 ].…”
Section: Introductionmentioning
confidence: 99%